Efficacy of ultrasonic cleaning on cockle shells - Hasan, Mohamad Rais; Che Abdullah, Che Azurahanim; Nor Afizah, Mustapha; Mohd Ghazali, Mohd Sabri; Noranizan, Mohd Adzahan (Elsevier, 2023)
Processing technologies have contributed greatly to improving the efficacy of seafood processing. The conventional pretreatment step includes cleaning by boiling or chemical immersion. Cockle shells are composed of calcium-rich materials with the potential to be used for producing various kinds of innovative seafood products (ISP). Therefore, cleaning the shells at the pretreatment step is crucial to ensuring safety and quality by removing contaminants beforehand. This study aims to evaluate the efficacy of ultrasound as a decontamination technique for cleaning cockle shells. Samples were separated into control and ultrasonic groups, and treated for 15 and 25 min. The ultrasonication was done in two modes, i.e., i) continuous (0.18 W/cm2 , 0.35 W/cm2 , 0.41 W/cm2 ), and; ii) pulse (0.35nullW/cm2 , 1:1 On-Off ratio). The efficacy of the decontamination was analyzed in terms of the whiteness index (WI), morphological characteristics, chemical composition, and turbidity of the wash water. Decontamination of the shells was achieved through physical effects i.e., erosion of the shell surface. The effective zone for ultrasonic cleaning was between 0.35 and 0.41 W/cm2 at 37 kHz for 15 min. The effectiveness of pulsed mode with the same actual power for cleaning is considered time-dependent. Ultrasonic cleaning could be a useful tool to clean cockle shells. This approach functions as a pre-treatment step for various innovative products from seafood processing.